Enhancing the selectivity for light olefins through catalytic cracking of n-hexane by phosphorus doping on lanthanum-modified ZSM-5 - Ali, Muhammad Faryad; He, Mu; Rizwan, Muhammad; Song, Yueqin; Zhou, Xiaolong; Asif Nawaz, Muhammad; Sun, Hui; Zhou, Mengke; Jiang, Peng (Frontiers in Chemistry, 2024)
Naphtha, as the primary source of producing light olefins, could well integrate their increasing demand through the energy-efficient process of catalytic cracking with ZSM-5. In the current work, different amounts of lanthanum and phosphorous were loaded on ZSM-5 using the wet impregnation method to tune the acidic properties of ZSM-5 for selective catalytic cracking of n-hexane to produce light olefins. Various characterization techniques such as XRD, Al NMR, NH3-TPD, Py-FTIR, ICP, N2 adsorption-desorption, XPS, and SEM were adopted to investigate the deeper insights of the modified zeolites. It was found that La addition in ZSM-5 to some extent (of 0.25 wt. % to 1 wt. %), improved the catalytic life and increased the n-hexane conversion (to 99.7%), while the further addition had a negative impact on reducing the conversion rate and deviating the product selectivity towards a significant amount of undesired BTX fraction (33%). On the other hand, the selectivity of light olefins was achieved up to 64% on phosphorous doped ZSM-5 (at a loading amount of 1 wt. %), while reducing the BTX fraction (2.3%) and n-hexane conversion of 69%. Since a dual metal modified ZSM-5 with optimal loading amount 1P0.25LaZ5 (phosphorus 1 wt. % and La 0.25 wt.%), was helpful in boosting the light olefins selectivity of 62% in the tuned Lewis acid sites at n-hexane conversion of about 77%, while decreasing the undesired BTX selectivity to 3% by reducing the number of Brønsted sites. Thus, the current study reveals that tuning the acidic sites of ZMS-5 by dual metal decoration P.La is an effective way of controlling the undesirable BTX amount at a stable n-hexane conversion and substantial olefins selectivity.